Impact of the Surgical Environment on the Incidence, Timing, and Severity of Complications Associated With Oromaxillofacial Oncologic Surgery in Dogs - Rigby, Brittney E.; Malott, Kevin; Sample, Susannah J.; Hetzel, Scott J.; Soukup, Jason W. (Frontiers in Veterinary Science, 2021)
Numerous reports describe complication rates associated with oromaxillofacial oncologic surgery in dogs, however, investigation regarding the impact of the surgical environment on the incidence of complications is under reported. The objective of this retrospective cohort study, including 226 dogs surgically treated for oromaxillofacial tumors between January 1, 1997 and December 31, 2018, is to evaluate the impact of the surgical environment on the incidence of complications in oromaxillofacial oncologic surgery in dogs. A secondary objective is to report the incidence of local complications in oromaxillofacial oncologic surgery and characterize the type, timing, and severity of complications encountered. Incidence of complications was identified to be 69.9%. No significant association was identified between the incidence, timing, or severity of complications and the training background of the clinician, physical location of the procedure, or the ostectomy instrument used. These results suggest that the surgical environment has little impact on the incidence, timing, and severity of complications in dogs undergoing oromaxillofacial oncologic surgery. The results also emphasize the importance of preparing the surgical team and the client for a high incidence of complications associated with oromaxillofacial oncologic surgery in dogs and indicate that both short-term and long-term follow up is important in these cases. Oromaxillofacial surgery performed by residents-in-training within a veterinary teaching environment with adequate supervision appears to be safe.